Cisplatin resistance in germ cell tumours: models and mechanisms. (29th December 2014) - Jacobsen, C.; Honecker, F.
Summary Recent years have led to a better understanding of the mechanisms underlying cisplatin response and resistance in germ cell tumours (GCT), and several promising targets have been identified. Two main mechanisms of the responsiveness to DNA damaging agents have been postulated. Firstly, GCT readily activate a DNA damage response, but show deficits in several damage repair pathways. In particular, they have been found to have defects in interstrand crosslink repair and in homologous recombination (HR). Secondly, GCT, especially embryonal carcinoma (EC) cells, show a hypersensitive apoptotic response to DNA damage, which activates p53, and leads to up‐regulation of the pro‐apoptotic factors Noxa, Puma and Fas in non‐resistant EC. These cells fail to activate p21 which induces a G1/S arrest, but accumulate in G2/M phase. In the absence of functional p53, family members like p73 and GTAp63 might be important in initiating this response. Mechanisms involved in cisplatin resistance are as follows: down‐regulation of Oct4 (e.g. as a result of hypoxia, treatment with retinoic acid or exposure to cisplatin) and failure to induce Puma and Noxa; changes in the expression levels of micro‐RNAs such as miR‐17/‐106b, miR‐302a, or miR‐371 to ‐373; elevated levels of MDM2 and cytoplasmic translocation of p21 by phosphorylation; and activation of the PDGFRβ/PI3K/pAKT pathway. Several approaches to overcome resistance have been successfully examined in vitro and in vivo, including PARP inhibitors, especially in cells showing deficient HR‐repair; stabilization of p53 using nutlin‐3; inhibition of several components of the PI3K/pAKT pathway using small molecules; and DNA demethylation by 5‐azacytidine or 5‐aza‐deoxy‐cytidine, among others. Many of these substances deserve further exploration, alone or in combination with DNA damaging agents, and the most promising approaches should be taken forward to clinical testing. Targeted therapy based on mechanistic insights holds the promise to turn cisplatin‐resistant GCT into a curable disease.